Penyuluhan Teknis Budidaya Ikan Air Tawar dan Pemasarannya Di Kabupaten Dogiyai - Tebai, Natan; Matakena, Simon; Sairdama, Syusantie Sylfia (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
This service program focuses on improving freshwater fish cultivation skills and marketing the results in Dogiyai Regency, which still experiences limitations in modern cultivation techniques and market access. The main objective of this activity is to increase the productivity and income of fish farmers through technical counseling, practical assistance, and improving marketing strategies. The methods used include training based on the theory and practice of modern fish cultivation, intensive mentoring in the field, as well as digital marketing training. The results of the service show a significant increase in community cultivation skills, increased fish production, and increased market access through digital platforms. In addition, this program contributes to the economic welfare of local breeders by increasing the selling value of fishery products